Straton z Sardes i Rufinos w świetle loci similes - Witczak, Krzysztof Tomasz (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
Strato of Sardis and Rufinus (of Samos?) were two Ionic poets, writing the erotic epigrams and preparing two different erotic anthologies. The former was the maker of the so called Musa Puerilis (preserved in AP, book XII , ep. 1–258) and the author of an anonymous preface (AP XII 1), the latter was the most probable creator of the Sylloge Rufiniana (attested in Anthologia Palatina [abbr.AP], book V, ep. 1–103) and the author of an anonymous preface (AP V 1). There are numerous resemblances in their erotic poetry, which document clearly that the one was familiar with the other’s epigrams. The following similar items are compared and discussed in this article: (a) AP V 9~ AP XII 226; (b) AP V 12 ~ AP XI 19; (c) AP V 21 ~ AP XII 229; (d) AP V 35, 36 ~ AP XII 207; (e) AP V 75 ~ AP XII 205, 250; (f) AP V 92 ~ AP XII 186. The author’s analysis demonstrates that Strato of Sardis was the borrower in three cases (a), (c), (d). It is acceptable, however, that Rufinus and Strato lived in Ionia in the same time. It is suggested that Rufinus’ collection was published somewhat earlier than Strato’s Musa Puerilis. If it is firmly established that Strato published his anthology of the pederastic poems under Hadrian (117–138 AD), then the most probably conclusionis that the Sylloge Rufiniana was edited by Rufinus himself most probably in two first decades of the 2nd century AD.
Keywords: epigram; Anthologia Palatina; Straton z Sardes; Rufinus; epigram erotyczny; homoerotyzm